KAJIAN PERLINDUNGAN HUKUM BAGI MASYARAKAT TERHADAP EFEK SAMPING PASCA PELAKSANAAN VAKSINASI COVID-19 DI INDONESIA - Hariman Alamsyah Siregar; Sugeng Hartono; Haura Taqiya Ramadina Siregar (CV. Denasya Smart Publisher, 2026)
Since the discovery of the SARS-CoV-2 virus in late 2019, the world has faced the COVID-19 pandemic, which has had significant health, social, and economic impacts. Efforts to control the spread of this virus include mass vaccination programs. However, as with all medications and vaccines, COVID-19 vaccines have the potential to cause side effects in a small number of recipients. While serious side effects are extremely uncommon, they still need to be considered when it comes to safeguarding public health. Objective: Additional research is necessary to examine how to safeguard against side effects from COVID-19 vaccination in Indonesia. This includes investigating compensation mechanisms and legal protections for those affected, understanding the government's role in managing vaccination risks, and exploring the steps individuals can take if they do not receive legal recourse following vaccination This study employs normative legal research methods, focusing on the analysis of legal texts, legal documents, and related norms to understand and interpret applicable legal principles. In Indonesia, legal protection against side effects from COVID-19 vaccination involves two primary components: preventive and repressive. Preventive measures are outlined in Presidential Regulation No. 99 of 2020, which sets standards for vaccination practices and BPOM oversight to reduce risks. Repressive measures include administrative penalties for failing to comply with vaccination requirements, as defined in Presidential Regulation No. 14 of 2021. Additionally, Article 15B of this regulation provides for compensation in cases of disability or death resulting from vaccination. Ministerial Regulation No. 10 of 2021 further details the process for claiming compensation. The government plays a key role in managing vaccination risks, but if legal protection falls short, individuals can pursue compensation through civil suits, citizen lawsuits, or class actions. The legal protection system for post-vaccination side effects of COVID-19 in Indonesia includes comprehensive preventive and repressive measures. The effectiveness of this protection depends on consistent implementation and transparency in the compensation process. Although regulations and compensation mechanisms are well established, improvements in public education, supervision, and law enforcement are necessary to ensure optimal protection and justice for affected individuals.